2020
DOI: 10.3390/app10207063
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Size and Distribution of Silver Nanoparticles on the Surface of Titanium Implant Regarding Cell Viability

Abstract: Though the antibacterial effect is advantageous, silver and silver nanoparticles can negatively affect the viability of human tissues. This study aims to check the viability of cells on surfaces with different particle size and to find the biologically optimal configuration. We investigated the effect of modified thickness of vaporized silver and applied heat and time on the physical characteristics of silver nanoparticle covered titanium surfaces. Samples were examined by scanning electron microscopy, mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
(43 reference statements)
0
6
0
1
Order By: Relevance
“…The sample preparation for electron microscopy analysis was performed as described previously [ 35 ]. Briefly, the cell–containing samples were fixed with 2 v/v % glutaraldehyde for 2 h and at 1 m/m % OsO 4 , and then dehydrated using graded ethanol solutions, and their critical points were dried using CO 2 before the examination.…”
Section: Methodsmentioning
confidence: 99%
“…The sample preparation for electron microscopy analysis was performed as described previously [ 35 ]. Briefly, the cell–containing samples were fixed with 2 v/v % glutaraldehyde for 2 h and at 1 m/m % OsO 4 , and then dehydrated using graded ethanol solutions, and their critical points were dried using CO 2 before the examination.…”
Section: Methodsmentioning
confidence: 99%
“…Once the Ag NPs are found at the surface of the implant, due to their high reactivity, the ions will be released and will react with sulfur or oxygen from the bacteria structure. Hajdu et al [ 48 ] suggest that the electronic charges of Ag NPs can modify the hydrophilicity of the implant in order for the adhesion of proteins involved in the healing process to be added faster. The study also showed that the smallest Ag NPs used (around 60 nm) are presenting the most promising result in biofilm development prevention [ 48 ].…”
Section: Silver Nanoparticles Particularities Related To Shape Size A...mentioning
confidence: 99%
“…Hajdu et al [ 48 ] suggest that the electronic charges of Ag NPs can modify the hydrophilicity of the implant in order for the adhesion of proteins involved in the healing process to be added faster. The study also showed that the smallest Ag NPs used (around 60 nm) are presenting the most promising result in biofilm development prevention [ 48 ]. Hajtuch et al [ 49 ] performed an interesting comparison between three types of functionalization of Ag NPs in order to observe their activity and influence on platelets function, for applications in the circulatory system.…”
Section: Silver Nanoparticles Particularities Related To Shape Size A...mentioning
confidence: 99%
“…It has been reported in the literature that smaller particles cause higher toxicity than larger particles. 64 Park et al In his study, he examined the toxic effect of Ag NPs of different sizes (20, 80, 113 nm) on L929 fibroblast cells. reported that 20 nm Ag NPs were more toxic than larger NPs.…”
Section: Cytotoxicity (Cell Viability) Of All Pva/nacas Nanofibersmentioning
confidence: 99%